The economic impacts of woodchip storage optimization: Reducing material and energy loss during transportation and storage - Torben Jensen (The Forestry Chronicle)
The use of woody biomass for domestic bioenergy provides many benefits and opportunities, but also presents a challenge regarding the supply chain required for maintaining the high quality feedstock for sustained bioenergy production. This article focuses on one aspect of that supply chain – woodchip storage. To encourage the establishment of a bioenergy market and to help ensure a safe and stable fuel source, Suzanne Wetzel and Christopher Helmeste from the Canadian Forest Service, Canadian Wood Fibre Centre (CFS/CWFC) and collaborators contributed their scientific expertise to the development of a solid biofuels guide based on existing national standards from the Canadian Standard Association’s (CSA). This paper explores the potential economic impacts for bioenergy producers of implementing the CSA guidelines. These impacts include reducing material and energy loss during transportation and storage. Potential benefits were determined by cost-benefit analysis. The results of this economic impact study have significant potential implications for bioenergy producers, including the integration of economic considerations in the development of policies for biomass feedstock optimization for the Canadian bioenergy industry.